Built Environment and Loneliness Among Older Adults in South East Queensland, Australia. (November 2022) - Lam, Jack; Wang, Siqin
Objective: To examine characteristics of the built environment and investigate associations with loneliness among older adults.Methods: Drawing on geocoded data from the Household, Income and Labour Dynamics in Australia Survey and measures of neighborhood features retrieved from multiple publicly available sources, we conducted principal component and regression analyses to examine the associations between characteristics of the built environment and loneliness among older adults in South East Queensland, Australia.Results: Older adults living in compact neighborhoods with higher population and housing density, smaller land parcels, and more access to green space reported lower levels of loneliness. Compact and mixed land-use neighborhoods may increase people's exposure to and social interactions with surrounding people and the environment.Conclusion: The built environment provides the context for social interactions. Our study and findings inform research and suggest the development of interventions surrounding the built environment that could potentially help tackle loneliness in older adults.